Customizing a Program for Older Adults Living with Frailty in Primary Care - Jananee Rasiah; Tammy O'Rourke; Brian Dompé; Darryl Rolfson; Beth Mansell; Rachel Pereira; Titus Chan; Karen McDonald; Anne Summach (SAGE Publishing, 2021)
Coordination of primary care is essential to improving care delivery within health systems, especially for older adults with increased health/social needs. A program jointly funded by the Canadian Foundation for Healthcare Improvement and Canadian Frailty Network, was implemented in a nurse practitioner-led clinic to address the gap in frailty care for older adults. The clinic was situated within a health and social services organization with a mandate to enhance the quality of life of older adults living in the community. Through this program, a frailty assessment pathway and social/clinical prescriptions were implemented with necessary adaptations as a result of COVID-19.